Productivity, employment and taxes: A SVAR analysis of the trade-offs and impacts - Kari E.O. Alho; Nuutti Nikula (The Research Institute of the Finnish Economy (ETLA), 2007)
The paper considers time series evidence on the relationships, and possible trade-offs, between productivity and employment, and on the impact of taxes in this connection. First, a heoretical model is built for an open economy leading to the identification of technology, non-technology and labour and capital tax wedge shocks, as based on their long-run effects. Then structural VAR models are estimated for the EU-15 and some other OECD countries to infer the above relationships. Our conclusion is that there is in the EU a fairly uniform and significant short-run negative impulse on employment from a positive productivity shock, while this becomes smaller and statistically insignificant over time in most, but not in some member countries. The former situation is interpreted to be an indication of nominal and the latter that of real or structural rigidity in the economy. In the US, there is no such trade-off, either in the short or long run. The impulse response of the shocks in the tax wedge on labour in the EU-15 is a fairly sizeable and significant negative impact on employment both in the short and long run, while the effects of capital income tax shocks are negative on productivity, but not significant in statistical terms. – – How much does the Finnish forest cluster invest in biotechnology R&D activity, and what are the key application areas in the value chain?
Keywords: O49; H29; J20; 330; Productivity; employment; taxes; EU; Produktivität; Beschäftigung; Steuer; Schock; Theorie; EU-Staaten